Offre et fréquentation des transports publics bruxellois de 1950 à 2017 - Vincent Carton (Brussels Studies)
Based on STIB statistics since 1950, this article analyses the choices made in the area of public transport service. A network based almost exclusively on trams gradually became an underground-tram-bus service, which has once again reached the same coverage as in 1950 in terms of kilometres. Although there was soon a consensus regarding the underground, it did not compensate for the decrease in the service due to network operation economies in the 1980s. It is not enough to invest most of the means in one single mode, in particular if its territorial coverage is limited. Although the relationship between the improvement in service and an increase in clientele is not automatic, a conclusion emerges: in 68 years, STIB attracted more users on three occasions when it improved its service throughout the network, especially the frequencies of trams and buses, as the underground frequencies have always been high. The study sheds light on the debate regarding the possible choices: should there be an investment in an underground line between Albert and Bordet or in the surface network (extension via lines with "high-level service", protection of trams and buses from traffic and increase in frequencies)?